2009
DOI: 10.1159/000265679
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Burden of Worn Therapeutic Silver Textiles for Neurodermitis Patients and Evaluation of Efficacy of Washing

Abstract: To reduce pruritus and colonization with Staphylococcus aureus, textiles containing silver are increasingly used as therapeutic option for patients with atopic dermatitis (AD). While wearing such textiles, the contained silver is in close contact with the patient’s skin. The silver serves two purposes: to reduce bacterial colonization of the skin, and to prevent contamination of the textile with ensuing growth of microorganisms. It is unknown whether the silver impregnation is able to reduce bacterial contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Silver textiles act by releasing silver ions onto the patient's skin . For reasons of hygiene, household machine washing is crucial to keep the clothing clean of bacteria . Therefore, clinically useful silver textiles must be resistant to household washing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver textiles act by releasing silver ions onto the patient's skin . For reasons of hygiene, household machine washing is crucial to keep the clothing clean of bacteria . Therefore, clinically useful silver textiles must be resistant to household washing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a previous study showed that the amount of bacteria present on the unwashed silver-containing fabric 'Juzo Skin Protect Silver' was lower than on placebo fabrics. 11 This might correspond to a possible destruction of the silver coating due to aggressive knitting, depend on the technology and machinery used, or result from the suboptimal release of Ag + antibiotic ions from certain types of fibres. Latest customized and milder knitting techniques might lead to the production of more stable functional textiles.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 days of wearing the placebo textile, the inside yielded 385.6±63.5 CFU and 236.5±49.9 CFU S. aureus , and 279.9±78.7 CFU and 119.3±39.4 CFU S. aureus were detectable on the silver textile. By daily washing at 60°C with conventional laundry detergent, contamination in both cases was almost completely eliminated [1]. …”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of antimicrobials into everyday products, such as the coating or impregnation of surfaces in refrigerators and food-storage containers to prevent mold infestation or bacterial decay, the antibacterial impregnation of sport socks to avoid odor, or weaving silver threads into textiles as a supportive treatment of atopic dermatitis [1], is increasing. Similarly, antimicrobial impregnation of surfaces, textiles, and clothing in the hospital is increasingly advertised as being able to prevent infection through their antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Daeschlein et al fokussierten auf die Fragestellungen, inwieweit es durch das Tragen von Silbertextilien bei Patienten mit Neurodermitis zu einer bakteriellen Kontamination kommt und auf die Wirksamkeit verschiedener Waschverfahren (maschinell vs. Handwäsche) . Die Ergebnisse zeigen, dass Silbertextilien im Vergleich zu Kontrolltextilien ohne Silber nach zwei Tagen ohne Waschung zwar weniger S. aureus aufwiesen, die Kontamination aber dennoch unerwartet hoch war, so dass hier von einem Rekontaminationsrisiko ausgegangen werden muss.…”
Section: Bewertungen Einzelner Therapieverfahren Zur Medikamentösen Tunclassified